EFEKTIVITAS PENGENDALIAN INTERNAL PEMUNGUTAN PAJAK REKLAME PADA UNIT PELAYANAN PEMUNGUTAN PAJAK DAERAH KELAPA GADING - Josua Rolamdo (2021)
The purpose of this study was to determine the tax collection systems and procedures in support of good internal control efforts at The Kelapa Gading Regional Tax Collection Service Unit. The method used in this research is qualitative by using an ethnometodological approach to explore the understanding of the actors on their direct involvement in the advertisement tax collection process using an interpretive paradigm. The focus of this research includes the advertisement tax collection systems and procedures, the elements of internal control, the components of internal control. The research data is in the form of primary data obtained through interviews, observations and documentation. While secondary data is in the form of objectives and realization of advertisement tax revenue, various regional regulations and governor regulations. The results of this study indicate that the internal control of The Kelapa Gading Regional Tax Collection Service Unit advertisement tax collection is effective. The use of a advertisement management information system can assist employees in monitoring and knowing taxpayers who are still in arrears of taxes. However, there are still some components of control that are not optimal.